Carburizer for aluminum and aluminum alloys

CN122979816APending Publication Date: 2026-10-27高宏 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510456903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

常规方式是选择石墨、石墨烯、石油焦、煤、煤焦粉和木炭等各种各样的碳粉加入铝合金中,采用熔融搅拌、低温搅拌、低温等离子渗透、3D打印+热处理、熔融+大电流辅助等方式,但效果不佳,因为碳与铝的渗透角度过大,铝水无法浸润碳,碳元素无法真正融入铝合金,现在已有的铝合金都视其中所含的碳为杂质,在铝合金中起破坏铝合金理化性能的作用,碳是尽量排除的元素,碳原子和铝原子无法形成稳定的化合物、络合物或中间合金物或未知的形态存在

Benefits of technology

[0014]有益效果:本发明将氯化盐和碳一起作为渗碳剂,含有氟化盐的碳粉颗粒具备了渗透进入铝合金的功能,能够和铝结合更好, 为此申请人做了相关试验如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979816A_ABST
    Figure CN122979816A_ABST
Patent Text Reader

Abstract

The application discloses a carburizing agent for aluminum and aluminum alloy and belongs to the technical field of metallurgy, and is characterized by comprising fluorinated salt and carbon. Through the carburizing agent, carbon can be added into aluminum and aluminum alloy, and the carbon content can be detected. Secondly, the aluminum alloy added with the carburizing agent can obviously refine the aluminum alloy grain as shown by the photo contrast, and the tensile resistance, tensile rate and bending resistance of the aluminum alloy can be optimized as shown by the tensile test. According to the analysis and speculation of the applicant, the modified carbon powder particles infiltrated by the molten electrolyte can penetrate into the aluminum alloy, so that the modified carbon atoms and aluminum atoms can form a compound or a complex or other unknown stable forms, the combination of aluminum and carbon can be more stable, and the aluminum alloy can be fundamentally changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgical technology, specifically relating to carburizing agents for aluminum and aluminum alloys. Background Technology

[0002] Electrolytic aluminum is the raw material for producing aluminum materials and aluminum alloys. Aluminum is a metal with low strength and good ductility. Besides the use of pure aluminum, it is alloyed to improve strength or overall performance. Adding one or more alloying elements to aluminum alters its microstructure and properties, making it suitable for various processed materials or cast parts. Commonly added alloying elements include copper, magnesium, zinc, silicon, and more than 40 other elements. Currently, aluminum alloys are classified into nine series, representing alloys with copper, manganese, silicon, magnesium, etc., as the main alloying elements. However, none of these nine series contain carbon.

[0003] Domestic and international companies and research institutions have long attempted to incorporate carbon into aluminum alloys, but without substantial breakthroughs. Conventional methods involve adding various carbon powders such as graphite, graphene, petroleum coke, coal, coal coke powder, and charcoal to the aluminum alloy, employing techniques like melt stirring, low-temperature stirring, low-temperature plasma infiltration, 3D printing combined with heat treatment, and melting combined with high-current assistance. However, these methods have yielded unsatisfactory results because the penetration angle between carbon and aluminum is too large, preventing the molten aluminum from wetting the carbon and ensuring that the carbon element cannot truly integrate into the aluminum alloy. Existing aluminum alloys generally consider the carbon content as an impurity, believing it to damage the alloy's physicochemical properties. Carbon is an element that is largely excluded, as carbon atoms cannot form stable compounds, complexes, intermediate alloys, or exist in unknown forms with aluminum atoms. Therefore, existing carbon-containing aluminum alloys cannot be considered true alloys, exhibiting various defects such as poor shock resistance, poor heat resistance, and poor flexural strength. Furthermore, unlike steel, they cannot retain carbon after melting, preventing it from separating and floating out due to differences in density. To date, they have not been able to be practically applied.

[0004] Patent application number 201110360403.3 discloses a low-temperature surface carburizing method for titanium-aluminum based intermetallic compound materials, including the following steps: (1) surface nano-sizing of the TiAl-based alloy surface using conventional equipment and methods; (2) low-temperature carburizing of the nano-sized TiAl-based alloy at 500℃~800℃ to prepare a carburized layer of 4~9µm thickness on the sample surface. Such treatment only infiltrates a micron-level carbon layer on the material surface and cannot be considered a carbon-containing aluminum alloy. Summary of the Invention

[0005] The purpose of this invention is to provide an aluminum and aluminum alloy carburizing agent that can incorporate carbon into aluminum alloys and improve their performance.

[0006] The technical solution of the present invention: A carburizing agent for aluminum and aluminum alloys, comprising fluoride salts and carbon.

[0007] The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

[0008] The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

[0009] By weight, it comprises 1-99% fluoride salts and 1-99% carbon.

[0010] By weight, it comprises 10-40% fluoride salts and 60-90% carbon.

[0011] By weight, it contains 20-30% fluoride salts and 70-80% carbon.

[0012] The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

[0013] The carbon is coal, graphite, or / and charcoal, one or more of which are mixed.

[0014] Beneficial effects: This invention uses chloride salts and carbon together as a carburizing agent. The carbon powder particles containing fluoride salts have the function of penetrating into aluminum alloys and can bond better with aluminum. To this end, the applicant has conducted relevant experiments as follows: 1. Recycle aluminum from aluminum wires, heat to 750℃ to melt and obtain primary aluminum. Cast the primary aluminum to obtain tensile test samples, which are used as the primary aluminum group. Add a mixture of cryolite and carbon powder to the primary aluminum at 750℃ in a weight ratio of 1000:100, stir thoroughly, and cast to obtain tensile test samples, which are used as the primary aluminum carburizing group. Add the samples from the primary aluminum carburizing group to the primary aluminum at a weight ratio of 1000:1000, remelt at 750℃, stir thoroughly, and cast to obtain tensile test samples, which are used as the primary aluminum carburizing dilution group.

[0015] The mixture of cryolite and toner is in a weight ratio of 100:100. It is obtained by melting cryolite and then adding toner and stirring. The toner particle size is 120.

[0016] Tensile tests were conducted on three groups of test specimens according to GB / T 228.1-2021 Metallic materials—Tension testing—Part 1: Test at room temperature. The results are shown in the figures below. Figure 1-3 The test results show that carburized aluminum can significantly improve its tensile strength and upper and lower yield strength. Low-magnification photographs of the original aluminum group, the original aluminum carburized group, and the original aluminum carburized diluted group are shown below. Figure 4-6Uncarburized aluminum alloys exhibited significantly coarse grains, while carburized aluminum alloys showed significantly fine grains. The aluminum alloys after carburizing, dilution, and recasting also showed significantly fine grains. Samples from the original carburized aluminum group and the original carburized and diluted aluminum group were sent to the Guizhou Provincial Institute of Analysis and Testing for carbon content analysis. The results are shown below. Figure 7 and 8 The carbon content of the primary aluminum carburizing group is 0.052; the carbon content of the primary aluminum carburizing dilution group is 0.0075.

[0017] 2. Aluminum alloy 350 purchased from Guiyang Huaheng Machinery Manufacturing Co., Ltd. was melted at 750℃ and cast to obtain tensile test samples, which served as the aluminum alloy 350 group. A mixture of cryolite and carbon powder was added to the molten aluminum alloy 350 at a weight ratio of 1000:100, stirred thoroughly, and cast to obtain tensile test samples, which served as the aluminum alloy 350 carburizing group. Samples from the aluminum alloy 350 carburizing group were added to the primary aluminum from Test 1 at a weight ratio of 1000:1000, stirred thoroughly, and cast to obtain tensile test samples, which served as the aluminum alloy 350 carburizing dilution group.

[0018] Tensile tests were conducted on the samples from the aluminum alloy 350 group, the aluminum alloy 350 carburized group, and the aluminum alloy 350 carburized dilution group. The results are shown in the table below. Figure 9-11 The test results show that carburized aluminum alloy 350 can improve both tensile strength and upper and lower yield strength. Samples from the carburized aluminum alloy 350 group and the carburized diluted aluminum alloy 350 group were sent to the Guizhou Provincial Institute of Analysis and Testing for carbon content analysis. The results are shown below. Figure 12 and 13 The carbon content of the aluminum alloy 350 carburizing group is 0.018; 0.031, and the carbon content of the aluminum alloy 350 carburizing dilution group is 0.0084; 0.014.

[0019] Experiments revealed that, firstly, carbon can be added to aluminum and aluminum alloys through the carburizing agent treatment of this invention, and the carbon content can be detected, but the carbon dilution ratio is unstable. Secondly, the addition of the carburizing agent to the aluminum alloy, as shown in photographic comparison, indicates that carbon can significantly refine the aluminum alloy grains. Tensile tests show that it can optimize the tensile strength, elongation, and flexural strength of the aluminum alloy, but the specific optimization effect of carbon content on the aluminum alloy is uncertain. The applicant speculates that the carbon powder particles, wetted by the molten electrolyte, may have been modified to possess the ability to penetrate into the aluminum alloy, allowing the modified carbon atoms and aluminum atoms to form compounds or complexes, or other stable forms of unknown structures. This makes the bond between aluminum and carbon more stable, fundamentally altering the aluminum alloy. The applicant will follow up and verify these reasons in subsequent research and experiments. Attached Figure Description

[0020] Figures 1-3These are the tensile test records for the primary aluminum group, the primary aluminum carburized group, and the primary aluminum carburized dilution group, respectively. Figures 4-6 These are low-magnification photographs of cross-sections of samples from the primary aluminum group, the primary aluminum carburized group, and the primary aluminum carburized diluted group. Figure 7 yes Figure 5 Carbon content test report of carburizing samples from Zhongyuan Aluminum Group; Figure 8 yes Figure 6 Carbon content test report of Zhongyuan Aluminum carburizing dilution group samples; Figures 9-11 These are the tensile test records for the aluminum alloy 350 group, the aluminum alloy 350 carburized group, and the aluminum alloy 350 carburized dilution group, respectively. Figure 12 This is the carbon content test report for the 350 aluminum alloy carburizing sample. Figure 13 This is a carbon content test report for the 350 aluminum alloy carburizing dilution group sample. Detailed Implementation

[0021] The present invention will be further described below with reference to embodiments and comparative examples, but these are not intended to limit the present invention. Example

[0022] A carburizing agent for aluminum and aluminum alloys, comprising fluoride salts and carbon.

[0023] The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

[0024] The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

[0025] By weight, it comprises 1-99% fluoride salts and 1-99% carbon.

[0026] By weight, it comprises 10-40% fluoride salts and 60-90% carbon.

[0027] By weight, it contains 20-30% fluoride salts and 70-80% carbon.

[0028] The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

[0029] The carbon is coal, graphite, or / and charcoal, one or more of which are mixed.

[0030] The particle size of the toner is 40-300 mesh.

[0031] By weight, carbon accounts for 40%-0.001% of aluminum. Adding carbon to aluminum and aluminum alloys can improve their tensile strength, elongation, and flexural strength, but the specific optimization effect of carbon content on aluminum alloys is currently uncertain. Therefore, when the carbon content in aluminum-carbon alloys is high, they can be used as intermediates for subsequent production of other aluminum alloys. When the carbon content in aluminum-carbon alloys is high, the appropriate carbon content should be selected based on the different contents of aluminum and aluminum alloys to obtain aluminum alloy materials with better performance. For example, in the experiment, adding about 0.01-0.03% carbon to recycled primary aluminum and aluminum alloy 350 can improve the tensile strength and upper and lower yield strength of the aluminum alloys.

[0032] In use, the fluoride salt is heated to a molten state (temperature reaches 750℃~1200℃), and then carbon powder is added to the fluoride salt and stirred, so that the fluoride salt is infiltrated into the carbon powder particles and absorbed by the carbon powder particles. The carbon powder particles that have absorbed the fluoride salt are added to the molten aluminum alloy. At this time, the carbon powder particles containing fluoride salt are modified to have the function of allowing carbon to penetrate into the aluminum alloy, so that aluminum and carbon form stable compounds, complexes, intermediate intermetallic compounds, or other unknown stable forms of substances. The carbon in the carbon-containing aluminum alloy formed will not separate from the aluminum due to the remelting of the aluminum alloy, and the carbon will not float out of the aluminum liquid, causing the recast carbon-containing aluminum alloy to lose its original properties. Example

[0033] One or more of the following fluorosilicates, fluorotitanates, or fluoroborates, such as sodium fluorosilicate, potassium fluorosilicate, sodium fluorotitanate, potassium fluoroborate, sodium fluoroborate, or potassium fluoroborate, are mixed with carbon powder (100-220 mesh) and used as a carburizing agent. In use, the fluoride salt is first melted and mixed with the carbon powder, then added to molten aluminum. Alternatively, the fluoride salt and carbon powder can be added directly to molten aluminum. The former method, where the aluminum electrolyte is melted and mixed with the carbon powder, shortens the reaction time between carbon and aluminum and improves the carburizing effect. By weight, the amount of carbon used is 30%-0.005% of the aluminum. Example

[0034] A carburizing agent is prepared by mixing and melting one or more of potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, or calcium fluoride, adding petroleum coke or coal coke powder, and using carbon powder with a particle size of 140-180 mesh. The carburizing agent is then added to the molten aluminum alloy, with the amount of carbon being 20%-0.01% of the aluminum by weight. Example

[0035] By weight, 10% fluoride salt and 90% carbon powder are mixed to obtain a carburizing agent. The fluoride salt can be potassium fluoride, lithium fluoride, sodium fluoride, or aluminum fluoride, one or more of these mixed together. The carbon powder can be graphite, petroleum coke, coal coke powder, or coal powder, one or more of these mixed together, with a particle size of 200 mesh. In use, the fluoride salt is first melted and mixed with the carbon powder, then added to molten aluminum. Alternatively, the fluoride salt and carbon powder can be added directly to molten aluminum. The former method, melting the fluoride salt and mixing it with the carbon powder, shortens the reaction time between carbon and aluminum and improves the carburizing effect. The carbon powder can be obtained by grinding substandard cathode carbon blocks and anode carbon blocks into powder. When using the carburizing agent, the amount of carbon, by weight, is 0.01-10% of the aluminum. Example

[0036] By weight, 20% fluoride salt and 80% carbon powder are mixed to obtain a carburizing agent. The fluoride salt is selected from the electrolyte produced by electrolytic aluminum, and the carbon powder is selected from cathode carbon blocks or anode carbon block waste ground into powder with a particle size of 150 mesh. Example

[0037] By weight, 30% fluoride salt and 70% carbon powder are mixed to obtain a carburizing agent. The carbon slag from the overhaul of electrolytic cells in aluminum electrolysis production, waste cathode carbon blocks, and anode residues are collected, crushed, and floated to obtain carbon powder containing fluoride salt. By weight, its composition is approximately 30% fluoride salt and 70% carbon powder, which can be directly used as a carburizing agent. Example

[0038] By weight, 40% fluoride salt and 60% carbon powder are mixed to obtain a carburizing agent. The carbon powder is made from coal, graphene, graphite, or charcoal. The fluoride salt is selected from fluorosilicates, fluorotitanates, or fluoroborates, one or a combination thereof, such as sodium fluorosilicate, potassium fluorosilicate, sodium fluorotitanate, potassium fluoroborate, sodium fluoroborate, or potassium fluoroborate. Example

[0039] By weight, 50% fluoride salt and 50% carbon powder are mixed to obtain a carburizing agent. The fluoride salt is sodium fluoride, aluminum fluoride, or cryolite, and the carbon powder is graphite or charcoal. Example

[0040] By weight, 60% fluoride salt and 40% carbon powder are mixed to obtain a carburizing agent. The fluoride salt is cryolite, and the carbon powder is graphite.

[0041] Example 10.

[0042] By weight, 70% fluoride salt and 30% carbon powder are mixed to obtain a carburizing agent. The fluoride salt is an aluminum electrolyte, and the carbon powder is carbon black.

[0043] Example 11.

[0044] By weight, 80% fluoride salt and 10% carbon powder are mixed to obtain a carburizing agent. The fluoride salt is a mixture of potassium fluoride and sodium fluoride, and the carbon powder is petroleum coke.

[0045] Example 12.

[0046] By weight, 90% fluoride salt and 10% carbon powder are mixed to obtain a carburizing agent.

Claims

1. A carburizing agent for aluminum and aluminum alloys, characterized in that, It includes fluoride salts and carbon.

2. The aluminum and aluminum alloy carburizing agent according to claim 1, characterized in that, The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

3. The aluminum and aluminum alloy carburizing agent according to claim 2, characterized in that, The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

4. The aluminum and aluminum alloy carburizing agent according to claim 1, characterized in that, By weight, it comprises 1-99% fluoride salts and 1-99% carbon.

5. The aluminum and aluminum alloy carburizing agent according to claim 4, characterized in that, By weight, it comprises 10-40% fluoride salts and 60-90% carbon.

6. The aluminum and aluminum alloy carburizing agent according to claim 3, characterized in that, By weight, it contains 20-30% fluoride salts and 70-80% carbon.

7. The aluminum and aluminum alloy carburizing agent according to claim 1, characterized in that, The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

8. The aluminum and aluminum alloy carburizing agent according to claim 7, characterized in that, The carbon is coal, graphene, graphite, or / and charcoal, one or a mixture of two or more of these.

Citation Information

Patent Citations

  • Low-temperature surface carburization method for titanium-aluminum-based intermetallic compound material

    CN102409282A